2000
DOI: 10.1016/s0735-1097(00)00632-x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow velocity immediately after primary coronary stenting as a predictor of ventricular wall motion recovery in acute myocardial infarction

Abstract: The coronary flow velocity pattern measured immediately after successful primary stenting is predictive of the recovery of regional and global LV function in patients with AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…14,15,26 The findings of the present study revealed that AMI is often complicated by congestive heart failure when microvascular injury is severe and that severe microvascular injury is always present when cardiac rupture occurs after recanalization. Probably for this reason, in-hospital death could be predicted more accurately from the CFV pattern, which allows a more quantitative assessment of microvascular injury, than from the angiographic contrast velocity.…”
Section: Yamamuro Et Al Coronary Flow and Patient Outcomesmentioning
confidence: 55%
“…14,15,26 The findings of the present study revealed that AMI is often complicated by congestive heart failure when microvascular injury is severe and that severe microvascular injury is always present when cardiac rupture occurs after recanalization. Probably for this reason, in-hospital death could be predicted more accurately from the CFV pattern, which allows a more quantitative assessment of microvascular injury, than from the angiographic contrast velocity.…”
Section: Yamamuro Et Al Coronary Flow and Patient Outcomesmentioning
confidence: 55%
“…Contrary to TIMI flow grade, myocardial blush grade, corrected TIMI frame counts and ST-segment resolution, coronary flow velocity under maximal vasodilation, our primary end point, is an objective quantitative measure of perfusion that, in the absence of coronary artery stenoses, reflects the integrity of the distal vascular bed. [5][6][7][8][9] In a previous study, coronary flow velocity under maximal vasodilation proved to be a sensitive parameter for the microcirculatory effects of abciximab that positively affected recovery of contractile function. 8 Even with this sensitive parameter of myocardial perfusion, we were unable to find a beneficial effect of the filter wire on coronary circulation during reperfusion.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 Despite restoration of large-vessel flow, tissue perfusion in area at risk frequently continues to be compromised, as shown by myocardial contrast echocardiography, 3,4 flow velocity measurements, [5][6][7][8][9] and assessment of TIMI frame counts 10,11 or myocardial blush. 12,13 Persistent microcirculatory impairment is associated with poor recovery of contractile function [3][4][5][6][7][8][9] and adverse clinical outcome. 3,10 -13 Apart from ischemic microvascular damage and reperfusion-induced regional inflammatory responses, distal embolization of plaque and thrombus material is considered a major cause of insufficient reperfusion despite a fully patent infarct-related artery.…”
mentioning
confidence: 99%
“…Likewise, it has been reported that the CFV pattern immediately after primary coronary stenting may be predictive of LV functional recovery during the healing phase of AMI. 12,15 More recently, the CFV pattern was found to be an accurate predictor of in-hospital complications and survival after AMI. 11 Here, we show that both in-hospital and long-term adverse clinical events can be predicted by the CFV pattern both qualitatively and quantitatively immediately after primary or rescue PTCA, establishing a relationship between the risk of adverse clinical events and microcirculatory function measured by intracoronary Doppler examination.…”
Section: Discussionmentioning
confidence: 99%